Airway management and functional outcomes in intubated patients with ischemic stroke - Jae Wook Jung; Ilmo Kang; Jin Park; Sang-Beom Jeon (Scientific Reports)
Abstract We investigated the functional outcomes in ischemic stroke patients who underwent endotracheal intubation according to airway management (i.e., extubation success, extubation failure, primary tracheostomy) at multiple time points. Patients were classified into three groups: extubation success, extubation failure, and primary tracheostomy. Their functional outcomes were compared at hospital discharge, 3-month, and 1-year. Out of 165 ischemic stroke patients, 84 (50.9%) underwent extubation attempt and 81 (49.1%) underwent primary tracheostomy. Among the patients who underwent extubation, 26 (31.0%) experienced extubation failure. The extubation success group had a higher rate of achieving a favorable functional outcome (modified Rankin Scale 0–4) compared to the extubation failure group at hospital discharge (adjusted odds ratio [aOR] 3.93; 95% CI, 1.33–13.1; p = 0.018) and at 3-month (aOR 5.67; 95% CI 1.79–19.8; p = 0.004), but not at 1-year (aOR 2.99; 95% CI 0.96–9.68; p = 0.061). The primary tracheostomy group had a significantly lower rate of achieving a favorable functional outcome at all time points compared to the extubation failure group. These findings suggest that a condition suitable for an extubation attempt may be a more important 1-year prognostic indicator than extubation failure. Despite its limitations, this study suggests that the clinical condition prompting primary tracheostomy may outweigh extubation failure as a determinant of 1-year prognosis. However, prospective studies are needed to validate it and clarify its clinical implications.